Differential Effects of Desaspidin on Photosynthetic Phosphorylation - Tsujimoto, Harry Y. (1966)
Sensitivity to low concentrations of desaspidin (5 × 10(−7)m) sharply distinguishes the photophosphorylations associated with the photooxidation of water from all other types of photophosphorylation by isolated chloroplasts. Contrary to recent reports in the literature, the effects of desapidin were not altered by changes in the redox conditions as influenced by the concentration of ascorbate and by the presence or absence of oxygen. Desaspidin consistently inhibited all types of cyclic photophosphorylation and the photophosphorylation coupled with the reduction of NADP by ascorbate-dichlorophenol indophenol. The same concentration of desaspidin gave little or no inhibition of photophosphorylation that are coupled with the photooxidation of water.